Pengembangan Handout Menggunakan Teknik Mnemonik Pada Materi Plantae - Rizkika, Mawadda Husnatul; Ali, Ahmad; Zulkarnaim, Zulkarnaim (Al-AHYA: Jurnal Pendidikan Biologi, 2023)
Students need to remember the lesson material by storing it in long-term memory using mnemonic techniques. This research aims to develop handouts using mnemonic techniques on class X Plantae material at SMAN 14 Maros that are valid, practical, and effective. The present study employs the ADDIE model for development research, which comprises five stages: analysis, design, development, implementation, and evaluation. The participants were 34 students from SMAN 14 Maros of class MIA 1. The tools utilized for the research included a validation form, questionnaires, and learning achievement tests. The findings showed that the developed mnemonic handouts have a high level of validity, with an average score of 3.7. Based on feedback from educators and students, the mnemonic handouts are considered highly efficient, with an average percentage of 88.7%. Furthermore, for effectiveness, the mnemonic handouts are categorized as highly successful, with a student pass rate of 94%. Therefore, these mnemonic handouts meet the requirements for use as they possess valid, efficient, and successful qualities.